Born oppenheimer and renner teller quantum dynamics of the ND plus D reaction - Hekim, Seda; Akpinar, Sinan (Elsevier Science Bv, 2019)
The Born Oppenheimer (BO) and Renner Teller (RT) time dependent quantum dynamics are investigated for the reaction ND(a(1)Delta) + D'(S-2), considering the NH2 electronic states (X) over tilde B-2(1) and (A) over tilde (2)A(1). The introduction of RT effects opens the possibility of studying not only the adiabatic reactions (depletion-A N(D-2) + D-2(a(1)Delta) and Exchange ND' + (a(1)Delta) + D) but also non-adiabatic ones (quenching + exchange ND'(X-3 Sigma(-)) + D, depletion-X N(S-4) + D-2(a(1)Delta)). The initial state resolved reaction probabilities, cross sections, and rate constants are obtained considering the Coriolis Coupling (CC) interactions for all the reactions above. To point out the role of RT and CC effect, we compared our results with experimental and semi-classical data.
Keywords: Real Wave-Packets; Conical Intersections; Surface; Predissociation